Experimental Investigation of Detonation Re-initiation Mechanisms Following a Mach Reflection of a Quenched Detonation - Bhattacharjee, Rohit Ranjan (Université d'Ottawa / University of Ottawa, 2013)
Detonation waves are supersonic combustion waves that have a multi-shock front structure followed by a spatially non-uniform reaction zone. During propagation, a de-coupled shock-flame complex is periodically re-initiated into an overdriven detonation following a transient Mach reflection process. Past researchers have identified mechanisms that can increase combustion rates and cause localized hot spot re-ignition behind the Mach shock. But due to the small length scales and stochastic behaviour of detonation waves, the important mechanisms that can lead to re-initiation into a detonation requires further clarification. If a detonation is allowed to diffract behind an obstacle, it can quench to form a de-coupled shock-flame complex and if allowed to form a Mach reflection, re-initiation of a detonation can occur. The use of this approach permits the study of re-initiation mechanisms reproducibly with relatively large length scales. The objective of this study is to experimentally elucidate the key mechanisms that can increase chemical reaction rates and sequentially lead to re-initiation of a de-coupled shock-flame complex into an overdriven detonation wave following a Mach reflection. All experiments were carried out in a thin rectangular channel using a stoichiometric mixture of oxy-methane. Three different types of obstacles were used - a half-cylinder, a roughness plate along with the half-cylinder and a full-cylinder. Schlieren visualization was achieved by using a Z-configuration setup, a high speed camera and a high intensity light source. Results indicate that forward jetting of the slip line behind the Mach stem can potentially increase combustion rates by entraining hot burned gas into unburned gas. Following ignition and jet entrainment, a detonation wave first appears along the Mach stem. The transverse wave can form a detonation wave due to rapid combustion of unburned gas which may be attributed to shock interaction with the unburned gas. Alternatively, the Kelvin-Helmholtz instability can produce vortices along the slipline that may lead to mixing between burned-unburned gases and potentially increase combustion rates near the transverse wave. However, the mechanism(s) that causes the transverse wave to re-initiate into a detonation wave remains to be satisfactorily resolved.
Keywords: Time resolved Schlieren photography; Reactive Mach Reflection; Gaseous detonation waves; Mach jet; Amplification mechanism